Injury and illness surveillance during the 24th Men's Handball World Championship 2015 in Qatar - Bere, T.; Alonso, J.-M.; Wangensteen, A.; Bakken, A.; Eirale, C.; Dijkstra, H. P.; Ahmed, H.; Bahr, R.; Popovic, N. (British Journal of Sports Medicine, 2015)
Background: The IOC encourages international federations to establish systematic athlete injury and illness surveillance programmes. Objective: To describe pattern of injuries and illnesses during the 24th Men's Handball World Championship 2015 by implementing the IOC injury and illness surveillance protocol. Methods: The medical staff of participating teams (n=24) were requested to report all new injuries and illnesses during matches and/or training on a daily basis throughout the event (15 January to 1 February, 2015). Exposure (number of player-hours) during all matches was calculated for all players (n=384) and for each of the 4 player positions (wing, back, line and goalkeeper). Results: Medical staff of all teams submitted 96.7% (n=325) of the daily report forms. In total, 27.1% of the players were injured, and of the 132 injuries reported, 40% were time-loss injuries. The total incidence of injuries was 104.5 per 1000 player-hours. The highest risk of injury was found among line players, and more injuries occurred during the first half of the matches. The most frequent injury location was the ankle, followed by the thigh, knee and head/face. The majority of injuries were contusion, sprain or strain. In total, 10.9% of the players were affected by an illness during the event. Of the 42 cases recorded, 31 (73.8%) were reported as respiratory tract infection. Conclusions: The risk of injury in handball is high among Olympic sports. Preventive measures should focus on contusions, ankle sprains, and thigh muscle strains, as well as measures aimed to reduce upper respiratory tract infections.